Profissionalização no terceiro setor: Um estudo de caso acerca das dimensões profissionalizantes em uma organização não governamental - Marques, Ricardo Ribeiro Rocha (2017)
The present research sought to investigate the dimensions of professionalization proposed by Melo (2013) from NGO Amigos de QuatroPatas, located in the municipality of São José do Egito/PE. This entity acts focused on the rescue and shelter of dogs and cats abandoned or born in the city streets. In virtue of its characteristics regarding the structure and management, aligned with the peculiarities of the third sector that sometimes jeopardizes the continuity of the organization, the NGO was faced with the need to professionalize itself. The professionalization of non-profit entities generates debates between defenders and opponents because of the possible consequences brought about by this process. In this study it was chosen to perform a qualitative research developed through the entity’s monitoring between the months of October 2015 and November 2016. It was used techniques such as participant observation and interviews based on the Melo (2013) approach conducted with those involvedwith the organization's management. Based on the collected data it was possible to see howthe organization has changed its management over time, ceasing to be guided by the assumptions of social management to assume a strategic character. As well as, through the experiences it has passed, it has demonstrated over the months a greater expression of professional aspects, among them the participation of cooperation networks, the appreciation of school course and the education level of the members, and the overcoming of primary sociability bonds that supported labor relations within the NGO.